Analysis of the Electronic Word of Mouth (E-Wom) Of the Film “KKN di Desa Penari” - Michelle Coritama; Daniel Susilo; Rismi Juliadi (LPPM Stikosa - AWS, 2022)
The film “KKN di Desa Penari” is based on a true story that went viral on Twitter in 2019. After being delayed for 2 years, the film “KKN di Desa Penari” premiered on April 30, 2022 and became the highest-grossing mystical film of all time. This film has the power of electronic word of mouth (e-WOM) through social media Twitter and YouTube in building virtual communities where people gather to respond and talk about the stories in this film. This study aims to determine the level of structure and groups in conversational communication networks. on Twitter and YouTube comments about the film “KKN di Desa Penari”. This research is a positivism paradigm research that uses a quantitative approach. The process of collecting data and visualizing data was using Netlytic and Gephi applications. The results of this study indicate that the density figure in the discussion about the film “KKN di Desa Penari” on Twitter with a low intensity of communication between actors. It is also seen that in the conversation on Twitter there are five actors with the highest indegree (intensity of being mentioned, retweeted or replied to), they are @habisnontonfilm, @simpem8137823, @Merapi_uncover, @onyoum_arkeeu and @luvfiqy. Meanwhile, YouTube user Willa Widiana has the highest indegree score on YouTube. However, no one showed a high outdegree (intensity of mentioning, retweeting or replying) either on Twitter or Youtube.